Assessment of Airflow Patterns Induced by a Retractable Baffle to Mitigate Heat Stress in a Large-Scale Mechanically Ventilated Barn - Seunghyeon Jung; Hanwook Chung; Christopher Y. Choi (Agriculture, 2023)
In large-scale dairy farming, heat stress remains a primary concern, and cross-ventilated barns have become increasingly prevalent in order to tackle this issue. Such barns employ energy-intensive electrical fans to enhance airflow and regulate temperature. To optimize this system, air baffles are often placed above the animal-occupied zones (AOZ) to direct airflow toward the cows. Although previous studies have suggested that baffles can substantially amplify the system’s cooling effect, the comprehensive impact of baffles on airflow patterns in a full-scale barn is less understood. Traditional measurement techniques, involving physical sensors, are both technically demanding and costly. Moreover, they often fall short in accounting for the dynamic microenvironmental changes induced by fluctuating weather, animal movement, and operational machinery. This study leverages computational fluid dynamics (CFD) to model airflow behaviors within a cross-ventilated barn, specifically examining the influence of a retractable baffle. CFD not only offers a reliable and efficient method for simulations but also allows for accurate assessments by validating the generated data against empirical observations. The results verify that, when properly configured, air baffles can significantly enhance airflow at cows in large barns. Additionally, the study establishes the reliability of CFD for designing large-scale dairy barns.